2020
DOI: 10.1038/s41598-020-70502-3
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-based in vivo model for drug-induced nephrotoxicity testing

Abstract: The need is critical and urgent for a real-time, highly specific, and sensitive acute kidney injury biomarker. This study sought to establish a sensitive and specific Miox-NanoLuc transgenic mouse for early detection of drug-induced nephrotoxicity. We generated Miox-NanoLuc transgenic mice with kidney-specific NanoLuc overexpression. Our data showed that Miox-NanoLuc-produced luminescence was kidney-specific and had good stability at room temperature, 4 °C, − 20 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“… Similarly, the levels of blood urea nitrogen (BUN) and creatinine (CRE) were comparable to those of the control groups, suggesting no signs of renal dysfunction (Figure S7B). Elevated levels of BUN and CRE are markers for nephrotoxicity or renal dysfunction …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Similarly, the levels of blood urea nitrogen (BUN) and creatinine (CRE) were comparable to those of the control groups, suggesting no signs of renal dysfunction (Figure S7B). Elevated levels of BUN and CRE are markers for nephrotoxicity or renal dysfunction …”
Section: Resultsmentioning
confidence: 99%
“…Elevated levels of BUN and CRE are markers for nephrotoxicity or renal dysfunction. 46 Troponin-I is involved in the regulation of cardiac muscle contraction, and high levels of serum troponin indicate myocardial injury. Qualitative immunoassay demonstrated an absence of troponin-I in the serum of treated mice, implying no signs of cardiac dysfunction (Figure S7E).…”
Section: Cancer-specific Dark and Light Toxicity Of G-cnqdsmentioning
confidence: 99%
“…Cisplatin mouse models have been used to investigate pharmacokinetics and tissue distribution of cisplatin [15][16][17], the repair capacity of cisplatin-DNA adducts [18], the molecular mechanisms of cisplatin toxicity [19][20][21][22][23] and to test a new generation of platinumbased chemotherapy drugs or adjunctive therapies [24][25][26][27][28][29][30][31][32][33][34][35], or other potential agents or strategies to prevent or treat cisplatin toxicities [36][37][38][39][40][41].…”
Section: Cisplatin Mouse Modelsmentioning
confidence: 99%
“…31,35 Previous studies investigating the mechanisms of AAN suggested that AAI acts mainly on proximal renal tubular epithelial cells 36,37 activating MAPK/extracellular signal-regulated kinase 1/2 (MEK/ERK1/2) signalling pathway, followed by depletion of intracellular GSH, 38 NQO1, CYP1A1/2, reduced organic anion transporters (OAT), inhibition of PI3K-Akt signalling, and activation of NF-κB, mitophagy, Rap1 signalling and TCA cycle. 31,[37][38][39][40][41][42] Several reports have proposed a role for the organic anion (OA) transporter (OAT) family in AA-mediated nephrotoxicity. 43,44 Recent evidence indicates that AA is concentrated within proximal tubular epithelial cells via the basolateral OAT (OAT1), which exchanges organic anions such as paraaminohippurate (PAH) and AA for α-ketoglutarate.…”
Section: Discussionmentioning
confidence: 99%